MEKANISME PROSES ALIGNMENT POROS MESIN ROTASI BERBANTUAN PERANGKAT LUNAK - Darto Darto; Sudjatmiko Sudjatmiko (INFO-TEKNIK, 2015)
The expected lifespan of the machine is very reliable and can be operated in order as long as possible without damage. Even systems "Maintenance Management" sophisticated yet become meaningless if the machines are not done properly alignment process. Approximately 70% of the causes of damage to machinery rotation due to misalignment.  Based on these conditions, the need for a method that is reliable and quick to make the process of alignment so that the production process does not experience the delay or shutdown process.          In order to do that then one way that can be done is by measuring alignment aided by using software. Alignment Quest is a mechanical device used to help straighten out the connection between one machine to another. Misalignment unnecessary, since misalignment is a major cause engine damage. By using the software can save money if the machines do not happen misalignment. Preventive maintenance of the machine will make the life of the engine becomes long.          Results of this study, the conclusion that the use of the software is technically Alignment Quest accelerate work in the process of rotation of the machine shaft alignment, the software will give you the results carefully if all measurement results dail indicator has high accuracy and the adjustment shim to add to the position of the machine directly viewable from the train folder. Keywords: engine rotation, alignment, software Alignment Quest